Kemampuan menggiring bola ditinjau dari keseimbangan dan koordinasi mata kaki - Hafidzullah, Muhammad Rijal; Sudarmanto, Eko; Fatoni, Muhad (Jurnal Porkes, 2024)
The purpose of this study was to examine dribbling ability in terms of balance and ankle coordination. The population used in this study were students who participated in extracurricular soccer totaling 30 boys. This research sample uses total sampling. The research method used is descriptive with a correlational study. The data collection technique uses a one-legged stand test (Stork stand), Foot-Eye Coordination Test, and Dribbling Skills Test. Data analysis uses prerequisite analysis tests, hypothesis testing. As a result, toe coordination obtained a median of 11 times, with the most achievements 14 times and the least 8 times. The average balance was 33.8“, with a maximum achievement of 60.5” and a minimum of 13.1. dribbling ability obtained an average of 17.35 “, with the fastest achievement of 19.7 and the longest 14.2. The conclusion is that there is a significant positive relationship between body balance and body balance and foot-eye coordination with dribbling ability. The implications of these findings can be used to improve training programs in the development of basic skills in primary school level football.